Memorie dislocate e biografie spezzate di Minori Stranieri Non Accompagnati - Roberta Altin (Archivio Antropologico Mediterraneo)
The article examines the violence and suffering experienced by unaccompanied foreign minors arriving by land in the cross-border area of Trieste. These are forms of structural violence, "layered" across space and time, starting with the causes of migration, the debts incurred to enable their departure, and the premature separation from their families to access the European international protection system, which is limited to a few categories, including minors. This compels many migrants to leave at an increasingly younger age to ensure they qualify for asylum, forcing them to endure survival challenges and dangers along the Balkan route, which becomes a true rite of passage into adulthood. Upon arrival in Italy, the ambivalent attitude that views them both as victims in need of protection and as petty criminals to be defended against reveals the structural violence embedded in the construction of European borders and citizenship.